In-situ reactions and mechanical properties of 6061 aluminum alloy weld joint with SiCp by laser melting injection. (May 2021) - Xu, Boan; Jiang, Ping; Geng, Shaoning; Wang, Yilin; Zhao, Jintian; Mi, Gaoyang
Abstract: In order to overcome weld joint softening of aluminum alloy, laser melting injection (LMI) methodology with 6H-SiC particles (SiCp ) and 6061 aluminum alloy was introduced. In this manufacturing, the molten pool morphology and temperature were gained by high speed camera and thermal imager. After LMI, a graded distribution of SiCp with 4.6%–4.8% volume fraction was obtained along the depth direction of weld. The aluminum grain under LMI (12.80 μm) was much finer than that under single laser welding (SLW) (40.94 μm). It was novel that the in-situ reactant Al4 C3 platelets would mainly locate discontinuously on the SiC/Al interface whereas acicular Al4 SiC4 was found primarily in the aluminum matrix. In addition, the nano-spherical simple substance carbon was precipitated around the surface of SiCp . Eventually, due to these particular in-situ reactions during laser welding with SiCp injection, the Vickers hardness of weld with SiCp was larger than that under SLW; a gradual hardness distribution in the depth direction of PRW was also observed; the tensile strength of weld with SiCp (192 MPa 243 MPa) became much higher without sacrificing ductility than SLW (165 MPa); the failure mechanism of weld with SiCp would change from SiCp cracking to the SiCp decohesion with the increasing welding speed. Graphical abstract: Unlabelled Image Highlights: The 2-3mm depth aluminum weld with SiC particles were manufactured firstly by laser melting injection. The process of laser melting injection could refine the aluminum grains compared with single laser welding. It was first discovered that Al4 C3 and Al4 SiC4 were distributed on the interface and in the metal matrix respectively. The in-situ reactions would result in the gradient distribution of hardness and the transformation of fracture mode.